The eukaryotic flagellum in health and disease - Farr, H (2007)
The 9 + 2 microtubule axoneme of flagella and cilia represents one of the most iconic structures built by eukaryotic cells and organisms. Some cilia are motile, whilst others serve as sensory organelles, and can variously possess 9+2, 9+0 axonemes and other associated structures. The recent emergence of ciliary dysfunction as a cause of human disease has renewed interest in these organelles, with several genomic and proteomic studies of cilia and flagella now published from various systems. I identified ten genes from such screens, and functionally characterised them in the flagellate protozoan parasite Trypanosoma brucei. One further gene was identified by searching a gene locus for polycystic kidney disease, a disease linked to malfunction of the primary cilium. I carried out a bioinformatic screen on the selected genes to determine their phylogenetic distribution. Cell lines expressing GFP fusion proteins were made to assess the localisation of this set of proteins, which were found to localise to a range of flagellar compartments including the axoneme and regions of the basal body. The well established inducible RNA interference system in T. brucei was then used to assess function of this set of proteins. In procyclic form trypanosomes the ablation of five proteins produced motility phenotypes when ablated; in some, but not all, this was accompanied by defects in axonemal ultrastructure. Two of these are closely related homologues and showed functional redundancy; when ablated independently there was no difference in motility, however simultaneous ablation produced flagellar paralysis. RNAi-mediated ablation of proteins affecting flagellar motility in bloodstream form trypanosomes produced rapid cytokinesis defects, suggesting that impairment of flagellar function may provide a novel avenue for disease control.